Combining pleasant Olfactory and BRAin stimulations in treatment-resistant depression (COBRA): study protocol for a randomized controlled trial - Imbert, Laetitia; Neige, Cécilia; Dumas, Maylis; Bensafi, Moustafa; Mandairon, Nathalie; Brunelin, Jérôme (Frontiers in Psychology, 2024)
Background Anhedonia, including social, physical, and less-known, olfactory, stands as a core symptom of major depressive disorder (MDD). At the neurobiological level, anhedonia has been associated with abnormal activity within the reward system, suggesting a key role for dopamine. Repetitive Transcranial Magnetic Stimulation (rTMS) has emerged as an innovative treatment for alleviating depressive symptoms. Stimulation of the dorsolateral prefrontal cortex (DLPFC) has been shown to both improve anhedonia and induce dopamine release. Moreover, research suggests that the efficacy of rTMS is improved when applied to an activated brain network rather than at rest. Our goal is to induce a dual activation of the reward system using a combined rTMS protocol and an intervention based on pleasant odorant exposure known to stimulate this system. Methods In this randomized controlled trial, we propose to combine rTMS targeting the left DLPFC with pleasant odorant stimulation to alleviate depressive symptoms. A total of 80 patients with treatment-resistant MDD will be randomly assigned to two groups and will receive 50 sessions of either: 1- rTMS and hedonic olfactory stimulations, or 2- rTMS alone. We will conduct pre- and post-assessments measuring depression severity, physical, social, and olfactory anhedonia, as well as the connectivity and activity of brain regions involved in the pathophysiology of depression and the reward circuitry. Discussion This study may strengthen the development of more effective rTMS interventions and pave the way for the establishment of rTMS combined with olfactory training as a safe, effective, and easily accessible treatment for MDD patients. In addition, this study will contribute to a better understanding of the mechanisms and physiopathology of MDD. Trial registration number #NCT05661383.